Density functional theory of the CuA‐like Cu2S2 diamond core in Cu 2II(NGuaS)2Cl2. Issue 11 (24th January 2016) - Witte, M.; Gerstmann, U.; Neuba, A.; Henkel, G.; Schmidt, W. G.
Abstract : Density functional theory (DFT) calculations with localized as well as plane‐wave basis functions are performed for the recently reported dicopper thiolate species Cu2 (NGuaS)2 Cl2 [NGuaS = 2‐(1, 1, 3, 3‐tetramethylguanidino) benzenethiolate, C11 H16 N3 S] and its bromo derivative [Neuba et al ., Angew. Chem. Int. Ed. 2012, 51, 1714.]. For both hybrid and semilocal functionals, the neutral complexes are found to have broken symmetry (BS) character, with electron paramagnetic resonance silent, antiferromagnetically coupled [Cu 2+ …Cu 2+ ] site in which the coupling is driven by super exchange interaction within the Cu2 S2 diamond core. The accurate theoretical description of the geometric structure, however, provides a major challenge for DFT: ( i ) the multideterminant character of the ground state wave function has to be covered by the BS approach. It requires ( ii ) metageneralized gradient approximations, that is hybrid functionals with an explicit dependence on the kinetic energy of the individual orbitals: In combination with a dispersion correction, the metafunctional TPSSh results in a CuCu distance close to the experimentally observed value of 2.7 Å. For the negative charge state of the complex, a mixed‐valent [Cu 1.5+ …Cu 1.5+ ] electronic structure with a smaller CuCu distance of 2.6 Å is predicted, similar to the value of the Cu A site of cytochrome c oxidase. © 2016 Wiley Periodicals, Inc. Abstract : Density functional theory calculations for the recently reported dicopper thiolate species Cu2 (NGuaS)2 Cl2 are performed to analyze the magnetic coupling and electronic structure of the Cu A ‐like Cu2 S2 diamond core. For both hybrid and semilocal functionals, the neutral complex provides an electronic structure with broken symmetry character. Within the antiferromagnetically coupled [Cu 2+ …Cu 2+ ] Cu‐site, the coupling is mainly driven by super exchange interaction within the Cu2 S2 diamond core.